Ответы и объяснения

2013-05-09T21:25:39+00:00

 Найдём производную и критические точки.

y'(x)=-sinx-\sqrt{3}cosx\\y'(x)=0\\-sinx-\sqrt{3}cosx=0\\-\frac{sinx}{cosx}-\frac{\sqrt{3}cosx}{cosx}=0\\-tgx-\sqrt{3}=0\\tgx=-\sqrt{3}\\x=arctg(-\sqrt{3})+\pi*n\\x=-\frac{\pi}{3}+\pi*n\\n=0,x=-\frac{\pi}{3}\\n=1,x=-\frac{2\pi}{3}

Подставим значения -\pi;-\frac{2\pi}{3};-\frac{\pi}{3};0 в функцию;

y(-\pi)=cos(-\pi)-\sqrt{3}sin{-\pi}=-1-\sqrt{3}*0=-1

y(-\frac{2\pi}{3})=cos(-\frac{2\pi}{3})-\sqrt{3}*sin(-\frac{2\pi}{3})=-\frac{1}{2}-\sqrt{3}*\frac{\sqrt{3}}{2}=-2

y(-\frac{\pi}{3}) =cos(-\frac{\pi}{3})-\sqrt{3}\sin(-\frac{\pi}{3})=\frac{1}{2}+\sqrt{3}*\frac{\sqrt{3}}{2}=\frac{1}{2}+\frac{3}{2}=2

y(0)=cos0-\sqrt{3}*sin0=1-\sqrt{3}*0=1

y_{max}=2\\y_{min}=-2

Вродебы так, я не уверен в некоторых углах.